Synthesis, characterization and investigation of mesomorphic and dielectric properties of novel biphenyl-based bent-core liquid crystals - Canli, Nimet Yilmaz; Ocak, Hale; Kara, Hasret; Bakirdogen, Gulsah; Eran, Belkiz Bilgin (SPRINGER, 2021)
The synthesis of novel biphenyl-based bent-core (BC) compounds 3 '-{4-[4-((S)-3,7-Dimethyloctyloxy)benzoyloxy]benzoyloxy}-4-{4-[4-(Octyloxy)benzoyloxy]benzoyloxy}biphenyl (DOB) and 3 '-{4-[4-((S)-3,7-Dimethyloctyloxy)benzoyloxy]benzoyloxy}-4-{4-[4-(Decyloxy)benzoyloxy]benzoyloxy} biphenyl (DDB) have been carried out. Mesomorphic properties of the novel BC compounds DDB and DOB were investigated using optical polarizing microscope and differential scanning calorimeter. The phase transition temperatures of both mesogens (DDB and DOB) exhibiting B-1 mesophase were determined, the dielectric parameters were studied, and calculations were made by dielectric spectroscopy technique on the cooling temperature range 135.04-62.81 degrees C and 141.45-64.83 degrees C, respectively. By calculation of the temperature-dependent real and imaginary parts of the dielectric constant, the change of the dielectric properties in the both LCs mesophase interval gradually have been revealed. Conductivity mechanisms have obtained with the help of frequency exponent values, s in selected temperature regions. The activation energies of (E-a) DDB and DOB at different temperature regions have also been estimated.
Keywords: CARBOXYL CONNECTING GROUPS; CROSS-COUPLING REACTIONS; POLAR ORDER; AC-CONDUCTIVITY; PHASES; MOLECULES; CHIRALITY; MESOGENS; FIELD; DIRECTION; Engineering; Materials Science; Physics